2001
DOI: 10.1002/aoc.185
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of aqueous inorganic mercury and methylmercury on suspended kaolin: influence of sodium chloride, fulvic acid and particle content

Abstract: The main tendencies in the adsorption of dissolved inorganic mercury (Hg 2 ) and methylmercury (MeHg ) on suspended kaolin particles have been investigated in synthetic aqueous solutions. The influence of NaCl, fulvic acid (FA) and suspended particulate matter (SPM) in the system has been studied at a constant pH of 7.2. The experiments were arranged according to a full factorial design with three factors (NaCl, FA SPM) at low (À) and high () levels. A central point (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 21 publications
2
8
1
Order By: Relevance
“…High concentration of Cl − in solution could also promote the formation of very stable MeHgCl complex which showed lower sorption than MeHg to MWCNTs. These results agreed with those of previous studies [20,48]. de Diego et al [48] found that a high concentration NaCl could led to declined adsorption rates of mercury species.…”
Section: Effect Of CL − On Adsorptionsupporting
confidence: 93%
See 1 more Smart Citation
“…High concentration of Cl − in solution could also promote the formation of very stable MeHgCl complex which showed lower sorption than MeHg to MWCNTs. These results agreed with those of previous studies [20,48]. de Diego et al [48] found that a high concentration NaCl could led to declined adsorption rates of mercury species.…”
Section: Effect Of CL − On Adsorptionsupporting
confidence: 93%
“…These results agreed with those of previous studies [20,48]. de Diego et al [48] found that a high concentration NaCl could led to declined adsorption rates of mercury species. Chen et al [20] revealed that the adsorption of Hg 2+ dropped drastically from 94.3% to 1.5% as the increase of Cl − concentration from 0 to 1.0 mol/L and as the pH increasing from 4.3 to 10.5.…”
Section: Effect Of CL − On Adsorptionsupporting
confidence: 93%
“…Despite the expectation that adsorption will be markedly lower in the presence of chloride ions due to HgCl 4 2-and RHgCl formation [13], this hypothesis was NaCl and an increase in Cl -concentration to 10 g L -1 had little effect (Fig. 4).…”
Section: Effect Of Anionsmentioning
confidence: 88%
“…Humic and fulvic substances, which form very strong complexes with mercury species, also influence their adsorption [13]. However, reports describing mercury adsorption under different conditions vary.…”
Section: Chemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation